Molecular Clues To Understand the Aerotolerance Phenotype of Bifidobacterium animalis subsp. lactis - Ruiz, Lorena (American Society for Microbiology, 2012)
Oxygen is one of the abiotic factors negatively affecting the survival of Bifidobacterium strains used as probiotics, mainly due to the induction of lethal oxidative damage. Aerobic conditions are present during the process of manufacture and storage of functional foods, and aerotolerance is a desired trait for bifidobacteria intended for use in industry. In the present study, the molecular response of Bifidobacterium animalis subsp. lactis IPLA4549 to aerobic conditions is presented. Molecular targets affected by oxygen were studied using two-dimensional electrophoresis (2DE) and quantitative reverse transcriptase (qRT) PCR. Globally, oxygen stress induced a shift in the glycolytic pathway toward the production of acetic acid with a concomitant increase in ATP formation. Several changes in the expression of genes coding for enzymes involved in redox reactions were detected, although the redox ratio remained unaltered. Interestingly, cells grown under aerobic conditions were characterized by higher activity of coproporphyrinogen III oxidase, which can directly detoxify molecular oxygen, and by higher NADH oxidase specific activity, which can oxidize NADH using hydrogen peroxide. In turn, this is in agreement with the glycolytic shift toward acetate production, in that more NADH molecules may be available due to the lower level of lactic acid formation. These findings further our ability to elucidate the mechanisms by which B. animalis copes with an oxygen-containing atmosphere.